A case study on the implementation of green building construction in Gauteng province, South Africa. Issue 3 (18th February 2020) - Masia, Thendo; Kajimo-Shakantu, Kahilu; Opawole, Akintayo
Abstract : Purpose: Green building is a relatively new concept with limited applications in property development in South Africa. The objectives of this study are therefore threefold: identify key green building principles considered by property developers, establish the benefits of implementing the principles and determine the barriers to its applications. Design/methodology/approach: The study adopted a case study of two Green Star South Africa (SA)-certified buildings in Sandton, Johannesburg. These are Alexander Forbes building, and Ernst & Young Eris Towers. The two certified buildings were purposefully selected because of the insightful information they provide regarding application of green building principles. The main themes investigated in the cases are environmental awareness, green building principles applications, as well as benefits and barriers of green building. A total of six interviewees from the contractors', property developers', environmental/green building consultants' and sustainability consultants' organizations who were involved in the implementation of green building principles in the two cases provided the qualitative data for the study. The qualitative data were supplemented with data relating to the two case studies obtained from the 'Earth Works for a Sustainable Built Environment'. The interviews were arranged over a period of two months, and each interview took between 20 and 30 minutes. Analysis of the data was done through a phenomenological interpretation of the qualitative opinions expressed by the interviewees. Findings: Key green building principles comprising energy efficiency, water efficiency, resource efficiency, occupants' health and well-being and sustainable site development were implemented in the two cases. The fact that the buildings were rated 4-star enabled inference to be drawn that the implementation of the principles was less than 60 per cent. Energy efficiency of 35 per cent indicated in Case I suggests that the level is consistent with the South African green building standard of 25 per cent to 50 per cent. However, the energy and water efficiency assessment of the building were based on projections rather than on ongoing monitoring and evaluation of the buildings' performance. Moreover, perceived saving in operational cost was identified as dominant driver to green building principles implementation. Conversely, lack of government incentives and absence of reliable benchmarking data regarding performance of green buildings were major barriers to its full implementation. Practical implications: The findings of this study provide important implications to the developers and government on the application of green building principles. In the first place, the evidence that initial high cost premium could be off settled by long- term saving on operational costs as a result of use of local materials, energy and water savings as well as use of recycled material, as implemented in the two case projects, would improve investment decision in green building by developers. The understanding of the drivers and barriers to implementation of green building principles also has implications for guiding government policies and programmes towards green building. Originality/value: The significance of this study stems from the fact that limited studies, especially in the South African context, have indicated the drivers and barriers to the implementation of green building principles. The case study approach adopted gave a novelty to the study by providing hands-on information from the stakeholders who were known to have played specific roles in the application of green building. The findings indicated that initial high cost premium was not a consideration in developers' choice of green building which justifies the possibility of a costlier product when factors such as environmental sustainability benefit is considered to be ultimate. The study thus suggests further research involving larger cases on energy efficiency, water efficiency and costs of green buildings compared to the conventional type to bring the findings to a broader perspective and assist to benchmark data for green building assessment.